2018
DOI: 10.1038/s41598-018-30518-2
|View full text |Cite
|
Sign up to set email alerts
|

Expression profiling of peripheral blood miRNA using RNAseq technology in dairy cows with Escherichia coli-induced mastitis

Abstract: E. coli is the main causative agent of mastitis in dairy cows, but the mechanism of molecular regulation underlying the occurrence and development of mastitis has not yet been fully elucidated. In this study, an E. coli-induced mastitis model was created and RNASeq technology was used to measure the miRNA expression profiles at different times post-infection (0, 1, 3, 5, 7 dpi), as well as to screen for differentially expressed miRNA. The results show detection of 2416 miRNAs, including 628 known miRNAs and 17… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 53 publications
5
27
0
Order By: Relevance
“…In agreement with the previous studies (Genini et al, 2011;Luoreng et al, 2018), the functional enrichment results of the darkgreen module reinforced that the "T cell receptor signaling pathway" might be involved in mastitis development. Accordingly, CD3E (Paquette et al, 2015), CD2 (Rivas et al, 2002), LCK (Nie et al, 2012), ZAP70 (Schulman et al, 2009), CD3D (Bonnefont et al, 2011), PRF1 (Twigger et al, 2018), CD8A (Kosciuczuk et al, 2017), and IL16 (Sharmila et al, 2002) were identified as highly connected genes of this module and also have been reported as important genes in immune response or mastitis development.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with the previous studies (Genini et al, 2011;Luoreng et al, 2018), the functional enrichment results of the darkgreen module reinforced that the "T cell receptor signaling pathway" might be involved in mastitis development. Accordingly, CD3E (Paquette et al, 2015), CD2 (Rivas et al, 2002), LCK (Nie et al, 2012), ZAP70 (Schulman et al, 2009), CD3D (Bonnefont et al, 2011), PRF1 (Twigger et al, 2018), CD8A (Kosciuczuk et al, 2017), and IL16 (Sharmila et al, 2002) were identified as highly connected genes of this module and also have been reported as important genes in immune response or mastitis development.…”
Section: Discussionsupporting
confidence: 91%
“…They are the predominant cell types found in the mammary glands during early stage of mastitis and recognize, adhere, and phagocyte invading pathogens (Medina, 2009). T cell receptor signaling pathway is related to adaptive immunity and has been reported as a candidate pathway associated with occurrence and development of mastitis in dairy cow (Luoreng et al, 2018). Additionally, in terms of individual highly connected genes identified in the blue module, several genes such as BIRC3, PSMA6, PSMB1, PSMD12, PSMD14, PSMD7 (Brand et al, 2011;Loor et al, 2011), EIF2S1 (Appuhamy et al, 2011), PTPRC (Nicholas et al, 2003), and CD53 (Rinaldi et al, 2010) have been reported as important genes in mastitis development.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The main bacteria causing mastitis in dairy cows are Streptococcus dysgalactiae, Streptococcus uberis, S. agalactiae, S. aureus , and E. coli ( 31 , 32 ); the latter three have been identified and studied by animal models ( 33 35 ). In particular, some studies have used phages to treat a mouse mastitis model caused by S. aureus and E. coli , which have shown therapeutic effects in vivo ( 25 , 36 , 37 ), indicating that the application of phages is safe and effective.…”
Section: Discussionmentioning
confidence: 99%
“…They originate from precursor miRNAs composed of 70 nucleotides (Berezikov 2011;Jin et al, 2014). Recent studies reported that some miRNAs associated with inflammation (i.e., miR-21, miR-146a, miR-155, miR-222, miR-383, miR-200a, miR-205, miR-122, and miR-182) were highly expressed in mastitis milk (Lai et al, 2017;Luoreng et al, 2018). The aim of this study was to determine the expression levels of these miRNAs in milk from Holstein-Friesian (HF) and Doğu Anadolu Kırmızısı (DAK) cows with subclinical mastitis caused by M. bovis and uninfected milk from these animals.…”
Section: Introductionmentioning
confidence: 99%